Characterization of the Pale Yellow Petal/Xanthophyll Esterase gene family in citrus as candidates for carotenoid esterification in fruits. (16th April 2021) - Zacarías-García, Jaime; Lux, Peter E.; Carle, Reinhold; Schweiggert, Ralf M.; Steingass, Christof B.; Zacarías, Lorenzo; Rodrigo, María J.
Highlights: Xanthophylls esters are the main carotenoids in orange-pigmented citrus fruit. Specific PYP/XES genes are ripening regulated in sweet orange and mandarin fruit. Transcript levels of PYP1, 2 and 6 are correlated with the carotenoid esters content in sweet orange. Expression of PYP in yellow citrus is in accordance with low xanthophyll-esters level. The PYP/XES are promising candidates for xanthophyll esterification in citrus. Abstract: In orange-pigmented citrus fruits, the xanthophyll esters are the predominant carotenoids, but their biosynthetic origin is currently unknown. In this work, seven PYP/XES ( Pale Yellow Petal/ Xanthophyll esterase ) genes were identified in Citrus genomes, but only PYP1-4 and 6 contained the structural domains essential for activity. The PYP/XES expression profiles in sweet orange and in other Citrus species such as lemon, mandarin and pummelo with marked differences in fruit pigmentation and content of xanthophylls esters, showed the upregulation of PYP1, 2 and 6 genes during ripening only in orange-pigmented fruits. Moreover, transcript levels of PYP1, 2 and 6 genes in peel and pulp of sweet orange were accompanied by the accumulation of xanthophyll esters during ripening. This work reports for the first time the PYP/XES gene family in C itrus and strongly suggests its involvement in xanthophyll esterification in citrus fruit tissues and its influence in carotenoid accumulation and fruit pigmentation.